Riba dan Bunga Bank Perspektif Neo-Modernis (Studi Kritik Pemikiran Fazlur Rahman dan Abdullah Saeed - Nur Kholis Majid (FAI, 2017)
Riba dan Bunga Bank Perspektif Neo-Modernis (Studi Kritik Pemikiran Fazlur Rahman dan Abdullah Saeed